Consumer Characteristics Of Financing Company Service Users In Indonesia - Wernat Newell Simamora; Ujang Sumarwan; Ma'mun Sarma (CV. Syntax Corporation Indonesia, 2023)
Abstract: Finance Company is a non-banking financial services company engaged in financing and is registered and supervised by OJK. The current challenge is the decline in the number of receivables and is inversely proportional to Financial Technology companies. Restrictive policies during the Covid-19 pandemic have made people change their purchasing behavior of goods and services, including credit transactions. The decline in the number of consumers in finance companies must be anticipated so that the company can maintain its market. The purpose of this study is to analyze the characteristics of consumers who choose Finance Companies as an alternative to obtaining loans. The research was conducted in an area with the largest population of Finance Company users, namely Jabodetabek . Data collection using the Cluster Random Sampling method using G-Form with a total of 200 respondents. The results of the study explained characteristics such as gender, age, education, occupation, marital status, income, and region of residence. Managerial implications that can be considered for finance service companies are that companies can find out consumer characteristics and obtain information in order to reach more consumers so as to provide benefits for the company.